Development of Inquiry Based-Metacognitif Skills on Water Pollution Materials for High School - Nur Subkhi; Lesy Luzyawati; Reza Shera Kusumaningrum (Mangifera Edu, 2022)
Metacognitive skills are essential in 21st-century education because they can hone students' reasoning. Metacognitive skills tend not to be trained much in the learning process and are not used to being assessed so that there is no instrument for assessing students' metacognitive skills. The research aims to develop a product of inquiry-based metacognitive skills on water pollution material, as well as to determine the feasibility of these instruments. This research method uses development research (R&D). The research samples were three lecturers as metacognitive skills experts, evaluation experts, and environmental experts, as well as two biology teachers in high school. The sampling technique was using a purposive sampling technique. Data collection techniques using validation sheets and interview sheets and validation sheets. Instrument products in the form of test sheets and observation sheets. The validation results show that the instrument product is at a very good level. It indicates that the inquiry-based metacognitive skills assessment instrument on water pollution material is suitable for use in schools.